A Population of Dipper Stars from the Transiting Exoplanet Survey Satellite Mission - Benjamin K. Capistrant; Melinda Soares-Furtado; Andrew Vanderburg; Marina Kounkel; Saul A. Rappaport; Mark Omohundro; Brian P. Powell; Robert Gagliano; Thomas Jacobs; Veselin B. Kostov; Martti H. Kristiansen; Daryll M. LaCourse; et al. (The Astrophysical Journal Supplement Series)
Dipper stars are a classification of young stellar objects that exhibit dimming variability in their light curves, dropping in brightness by 10%–50%, likely induced by occultations due to circumstellar disk material. This variability can be periodic, quasiperiodic, or aperiodic. Dipper stars have been discovered in young stellar associations via ground-based and space-based photometric surveys. We present the detection and characterization of the largest collection of dipper stars to date: 293 dipper stars, including 234 new dipper candidates. We have produced a catalog of these targets, which also includes young stellar variables that exhibit predominately burst-like variability and symmetric variability (equal parts bursting and dipping). The total number of catalog sources is 414. These variable sources were found in a visual survey of TESS light curves, where dip-like variability was observed. We found a typical age among our dipper sources of <5 Myr, with the age distribution peaking at ≈2 Myr, and a tail of the distribution extending to ages older than 20 Myr. Regardless of the age, our dipper candidates tend to exhibit infrared excess, which is indicative of the presence of disks. TESS is now observing the ecliptic plane, which is rich in young stellar associations, so we anticipate many more discoveries in the TESS data set. A larger sample of dipper stars would enhance the census statistics of light-curve morphologies and dipper ages.